The butterfly effect and earnings management: Analysis of long-term consequences of short-term adjustments - Ammar Razzaq Al Rubaye; Omar Adeeb Qassim; Salah Chyad Kadhim; Inas Mekee Abed (Heritage and Sustainable Development)
This paper investigates earnings management and its long-term consequences in the industrial sector of the MSM companies over a sample from 2011 to 2020. This study will test the effect of DAC, the most popular instrument employed in accounting practices for earnings management, on objective measures: return on assets and profit margin using Eviews 13 software. Suppose you have heard of the 'butterfly effect' from chaos theory. In that case, this will give you a grounding to understand how small financial changes can lead to massive unanticipated effects. Further, this study identifies how earning management activities are influenced by governance and transparency of company affairs by embedding firm size and leverage as moderators. These findings put forward the importance of the long-term consequences of short-term financial decisions, which is of real value to the literature on earnings.